How Everyday Counterfeit Behavior That Disrupts Self Authenticity Might Lead to Corruption Tendencies - Abraham, Juneman; Prayoga, Tommy; Murti, Kharisma; Azizah, Afifah; Krishti, Nathasya Shesilia; Fajrianti, Sheila Putri; Octaviana, Bernadette Nathania; Ispurwanto, Wing; Manurung, Rudi Hartono (Psychology research and behavior management, 2022)
In the field of moral psychology, researchers have strived to understand the complex dynamics of corruption psychology. This study contributes to this area by presenting a theoretical model for sequential behavior, placing counterfeit behavior (CB) as a predictor and corruption tendencies (proneness to moral emotions, ie, guilt and shame/GASP) as the criterion. In addition, two bridging variables are assigned, ie, inauthenticity/counterfeit self (CS) and moral disengagement (MD). The research applied a correlational-predictive design and mediation analysis. Study 1 involved 978 participants of Indonesian nationality (380 males, 598 females; = 23.64 years old, = 4.35 years), and found that GASP was predicted by MD, and MD was predicted by CS. Study 2, which applied a between-subject design, showed that CS was predicted by four kinds of everyday counterfeit behavior (backstabbing, fake listening, plagiarism, and religious hypocrisy). The hypotheses of Study 1 and Study 2 were confirmed by the data analysis. By integrating both studies, this study advocates the view of moral consistency through variable configuration (ie moral emotions, self and behavior authenticity, moral engagement) that composes corruption tendencies - which to the best of the author's knowledge, has not been proposed in other studies. The novelty contained in the variable network is that counterfeiting, which is present in our daily life and considered to be ordinary and inevitable in the 4.0 Industry era, has a critical disrupting implication towards a person's morality.